2017
DOI: 10.7717/peerj.2961
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of recombinant Persicaria minor β-sesquiphellandrene synthase

Abstract: BackgroundSesquiterpenes are 15-carbon terpenes synthesized by sesquiterpene synthases using farnesyl diphosphate (FPP) as a substrate. Recently, a sesquiterpene synthase gene that encodes a 65 kDa protein was isolated from the aromatic plant Persicaria minor. Here, we report the expression, purification and characterization of recombinant P. minor sesquiterpene synthase protein (PmSTS). Insights into the catalytic active site were further provided by structural analysis guided by multiple sequence alignment.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Also, it has been shown that at a lower temperature, mevalonate pathway genes are overexpressed in S. cerevisiae [ 36 ], providing more precursors to TASY. It is also likely that lower temperature has influenced TASY solubility, as was shown in previous studies for terpene synthase expression in E. coli [ 37 , 38 ]. Moreover, as there was a concurrent decrease in the titre of GGPP side product (GGOH) at 20 °C, at both shake flask and bioreactor cultivations (Figs.…”
Section: Resultsmentioning
confidence: 92%
“…Also, it has been shown that at a lower temperature, mevalonate pathway genes are overexpressed in S. cerevisiae [ 36 ], providing more precursors to TASY. It is also likely that lower temperature has influenced TASY solubility, as was shown in previous studies for terpene synthase expression in E. coli [ 37 , 38 ]. Moreover, as there was a concurrent decrease in the titre of GGPP side product (GGOH) at 20 °C, at both shake flask and bioreactor cultivations (Figs.…”
Section: Resultsmentioning
confidence: 92%
“…TPS-g subfamily is closely related to the TPS-b but lacks the N-terminal "R(R)X 8 W" motif and encodes MTPSs, STPSs, and DTPSs that produce mainly acyclic terpenoids [68,69]. A highly conserved arginine-rich RXR motif of sesquiterpene synthase reported that the motif is involved in producing a complex with the diphosphate group after the ionization of FPP in sesquiterpene biosynthesis [70]. TPS-g subfamily in Arabidopsis (AtTPS14) lacks both "R(R)X 8 W" and "RXR" motifs.…”
Section: The Evolution Of Tps Genes In Orchidaceae Speciesmentioning
confidence: 99%
“…Interestingly, although the sizes of Pm STPS1 and Pm STPS2 were different, the two enzymes produced similar sesquiterpene products (β-farnesene, α-farnesene, and farnesol, Figure 3 ), albeit at different percentages. Both Pm STPS1 and Pm STSP2 could catalyse the formation of β-farnesene, α-farnesene, nerolidol, and farnesol, whose functions were different from those of the previous STPS enzymes characterised in P. minus [ 36 , 37 , 38 , 39 ]. In addition, the enzymes demonstrated an inherent capacity for TPS enzymes to evolve different products and substrate specificities [ 57 ].…”
Section: Discussionmentioning
confidence: 79%
“…The DDxxD and NSE/DTE motifs flanked the entrance of the active site. In addition to these motifs, there was a highly conserved arginine-rich RxR motif, which was involved in the complexing of the diphosphate group, after the ionisation of FPP [ 18 , 39 ]. The RxR motif was located at 45 amino acids, upstream of the first DDxxD motif.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation